2019
DOI: 10.1044/2018_jslhr-s-18-0229
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Tongue Pressure According to Liquid Flow Properties in Healthy Swallowing

Abstract: Purpose During swallowing, the tongue generates the primary propulsive forces that transport material through the oral cavity toward the pharynx. Previous literature suggests that higher tongue pressure amplitudes are generated for extremely thick liquids compared with thin liquids. The purpose of this study was to collect detailed information about the modulation of tongue pressure amplitude and timing across the range from thin to moderately thick liquids. Method Tong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 47 publications
5
14
0
3
Order By: Relevance
“…Thus, the strength of the tongue and certain parameters observable by videofluoroscopic assessments were measured in healthy adult subjects (age range: 21-58 year.) while swallowing thickened water of different IDDSI Levels [51,52]. Consistent with previous literature [65], the results showed that the force exerted by the tongue during swallowing increased with the consistency of the liquid (n = 38) [52].…”
Section: Discrimination Ability Of the Iddsi Flow Testsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the strength of the tongue and certain parameters observable by videofluoroscopic assessments were measured in healthy adult subjects (age range: 21-58 year.) while swallowing thickened water of different IDDSI Levels [51,52]. Consistent with previous literature [65], the results showed that the force exerted by the tongue during swallowing increased with the consistency of the liquid (n = 38) [52].…”
Section: Discrimination Ability Of the Iddsi Flow Testsupporting
confidence: 89%
“…while swallowing thickened water of different IDDSI Levels [51,52]. Consistent with previous literature [65], the results showed that the force exerted by the tongue during swallowing increased with the consistency of the liquid (n = 38) [52]. However, this increase was not proportional in each of the IDDSI levels.…”
Section: Discrimination Ability Of the Iddsi Flow Testsupporting
confidence: 89%
“…Participants were instructed to take comfortable sips of thin, slightly thick, and mildly thick liquids, as well as comfortable teaspoons of moderately and extremely thick liquids, defined by the International Dysphagia Diet Standardisation Initiative (IDDSI) framework ( Cichero et al, 2017 ). Each cup was weighed before and after the participant took a sip to obtain measures of bolus weight, which were converted to bolus volume using published conversions ( Steele, Peladeau-Pigeon, Barbon, Guida, Tapson, et al, 2019 ). All liquids were mixed following standardized recipes ( Barbon & Steele, 2018 ) to a 20% weight-to-volume concentration of barium contrast (Bracco Diagnostics E-Z-PAQUE barium sulfate) and thickened with a xanthan gum thickener (Nestlé Resource ThickenUp Clear).…”
Section: Methodsmentioning
confidence: 99%
“…The nonbarium stimuli used in the study had a mild lemon flavoring, as judged by a blinded taste panel ( Steele et al, 2019 ). Although the intensity of sourness was significantly lower than has been previously reported to impact swallowing behaviors ( Nagy et al, 2014 ), the influence of taste cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol also involved the concurrent measurement of tongue-palate pressures using a three-sensor tongue bulb array placed with adhesive on the palatal surface. Data regarding measures of tongue pressure during swallowing have been reported in a separate manuscript ( Steele et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%